Myocardial Bridging: Tinjauan Mendalam Mengenai Anomali Koroner - Nurudinulloh, Akhmad Isna; Widito, Sasmojo (RSUD Dr. Saiful Anwar Province of East Java, 2024)
Myocardial bridging (MB) is a congenital coronary anomaly where segment of the epicardial coronary artery traverses through the myocardium for a portion of its length. While traditionally regarded as a benign condition, there is a growing focus on specific subsets of MB associated with ischemic symptoms and requires treatment. Increasing attention is being given to speciﬁc subsets of MB associated with ischemic symptomatology. The emergence of modern functional and anatomical imaging techniques; coronary angiography, coronary computed tomography angiography (CCTA), instantaneous wave-free ratio (iFR), dan diastolic fractional flow reserve (dFFR), has improved our capacity to characterize symptoms associated with MB. In cases involving symptomatic patients, medical therapy often represents an effective treatment option. For individuals who do not respond satisfactorily to medical interventions, comprehensive multimodal assessment; percutaneous coronary intervention (PCI), coronary artery bypass graft (CABG), and myotomy should be considered.